Optimal design of mast supported on prestressed anchorties - Loc, Dang Dinh (Vietnam Journal of Mechanics, 1984)
In this paper, the author uses the method of mathematical programming for the optimal design of a mast with prestressed anchorties. The objective function is the minimun cost or material volume of the whole post and ties. The restrictions are mechanical and technical requirements such as the conditions of strength and stability, the deflections of anchored knots. By applying the design method for a direct problem, the author has found out the efficient prestress in the ties, without any previous suppositions of theses their volume, as commonly resolved This optimal design would save 12% of the mast weight in comparison with other design.